Revisiting the Faculty’s Medical mobile clinic in its 3rd year of providing specialists clinical services in Johor - Ariffin, Farnaza @ Farnaz (Faculty of Medicine, 2025)
The Faculty of Medicine, UiTM medical mobile clinic is a project donated and funded by the Noah Foundation in collaboration with the Johor State Government. Since its inception in 2023, this initiative has been providing essential clinical services to communities in Johor.